The Role of Public Policy Communication in Poverty Alleviation - Hidayat, Rachmat; Dariyanto, Erwin (The Indonesian Forestry Certification Cooperation, 2023)
Poverty alleviation has become one of key global agendas for achieving sustainable development goals. Implementation of poverty alleviation programs, however, is often impeded by poor public policy communication. This study evaluates how public policy communication helps ensure the successful implementation of the programs, by reviewing (a) the importance of public policy communication, (b) the type of communication strategies implemented, and (c) the results gained. Using qualitative descriptive method, the authors review communication practices and results in Indonesia and other countries.